Athletes` rights protection in sport medical service system - Kuzmenko, V. I.; Musabirova, D. A.; Mukhametgaliyeva, S. Kh.; Ziganshin, B. G. (Theory and Practice of Physical Culture, 2018)
The study considers a few problems with concern to the professional athletes` health and life protection - particularly upon their retirement from professional sports. It is important to clearly specify and analyze the key problems of the health services to former professional athletes viewed as a specific health group, with such analyses being critical for bridging the gaps in the relevant legal provisions and law application practices to secure the valid legislation being applied on the most efficient basis with the lawful interests of every professional sport actor being respected on a balanced basis. Objective of the study was to analyze the theoretical and legal provisions for the sport health service to professional athletes. The practical study methods were dominated by the general theoretical (didactic) cognition method, comparative and logical structure analyses, plus analyses of the theoretical and practical studies in the subject field to secure the athletes` rights being duly protected by the health service system.